2021
DOI: 10.1016/j.ydbio.2021.06.005
|View full text |Cite
|
Sign up to set email alerts
|

A single-cell guide to retinal development: Cell fate decisions of multipotent retinal progenitors in scRNA-seq

Abstract: Recent advances in high throughput single-cell RNA sequencing (scRNA-seq) technology have enabled the simultaneous transcriptomic profiling of thousands of individual cells in a single experiment. To investigate the intrinsic process of retinal development, researchers have leveraged this technology to quantify gene expression in retinal cells across development, in multiple species, and from numerous important models of human disease. In this review, we summarize recent applications of scRNA-seq and discuss h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 208 publications
(362 reference statements)
3
20
0
Order By: Relevance
“…For each of the three main retinal cell types at this age, we see a cascade of TF motif representation in open chromatin as the cells develop from progenitors to a specific fate. The cascade of motif enrichment we observe for each cell type is consistent with many previously identified TFs known to be important in that cell lineage (Aavani et al, 2017;Shiau et al, 2021;Wu et al, 2021). Overall, there is a good correspondence in the sequence of expression of the most highly expressed TFs by scRNA-seq with the relative abundance of their motifs in accessible chromatin for these cell types (Figure S3A, p < 0.05; Table S3); the Z score of the accessibility in the clusters in a given lineage is significantly correlated with the average RNA expression for each cluster (Figure S3A; Table S3) across the major retinal cell lineages.…”
Section: Chromatin Accessibility At Early Stages Of Human Fetal Developmentsupporting
confidence: 87%
“…For each of the three main retinal cell types at this age, we see a cascade of TF motif representation in open chromatin as the cells develop from progenitors to a specific fate. The cascade of motif enrichment we observe for each cell type is consistent with many previously identified TFs known to be important in that cell lineage (Aavani et al, 2017;Shiau et al, 2021;Wu et al, 2021). Overall, there is a good correspondence in the sequence of expression of the most highly expressed TFs by scRNA-seq with the relative abundance of their motifs in accessible chromatin for these cell types (Figure S3A, p < 0.05; Table S3); the Z score of the accessibility in the clusters in a given lineage is significantly correlated with the average RNA expression for each cluster (Figure S3A; Table S3) across the major retinal cell lineages.…”
Section: Chromatin Accessibility At Early Stages Of Human Fetal Developmentsupporting
confidence: 87%
“…After embedding all the single cells into a common space, their visualization on UMAP revealed that the major cell types of the retina clustered together (Figure 4B and S4B). In line with the developmental birth order of retinal neurons and the Müller glial, we observed that fetal samples from up to approximately 100 days of conception contained high proportions of retinal ganglion cells, horizontal cells, and cones (in relation to rod cells) (Figure S4C) (Shiau et al, 2021). Rods, amacrine, bipolar, and Müller cells demonstrated increased proportions after the 100-day time point, in agreement with the knowledge that these cell types are late-born cells.…”
Section: Identifying Genes Associated With Human Retina Maturationsupporting
confidence: 86%
“…This knowledge base will provide the foundation for future studies on ocular pathology and development. Single cell techniques lend themselves to studies of organogenesis ( Haniffa et al, 2021 ) and scRNA-seq has already been successfully deployed to analyze the processes of competence, specification, and differentiation in the developing retina (Shiau et al, 2021) . It is to be expected that the inductive interactions that control the developmental trajectories of cells in the anterior segment will prove similarly amenable to analysis at the single cell level.…”
Section: Discussionmentioning
confidence: 99%